2002
DOI: 10.1046/j.0960-7412.2001.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 plays different roles in determining penetration failure in three diverse plant–fungal interactions

Abstract: Fungal plant pathogens that attempt to penetrate and feed on living cells frequently trigger a localized plant defence response that results in fungal penetration failure. In the current study we demonstrate that breakdown products of the cell wall released by the localized application of hemicellulase elicit localized responses including, sequentially, extracellular H2O2 generation; accumulation of phenolic compounds; and cross-linking of proteins in the cell wall. In a detailed time-course study of three pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
207
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(223 citation statements)
references
References 44 publications
8
207
0
1
Order By: Relevance
“…It has been showed that an accumulation of ROS plays a central role in a number of non-host interactions like barley/Blumeria graminis f. sp. tritici (Hück-elhoven et al 2001), cowpea/Erysiphe cichoracearum (Mellersh et al 2002); and pepper/Blumeria graminis f. sp. tritici pathosystems (Hao et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been showed that an accumulation of ROS plays a central role in a number of non-host interactions like barley/Blumeria graminis f. sp. tritici (Hück-elhoven et al 2001), cowpea/Erysiphe cichoracearum (Mellersh et al 2002); and pepper/Blumeria graminis f. sp. tritici pathosystems (Hao et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…mROS may contribute to plant defense by either directly acting against the pathogen or acting as a signaling molecule in plant defenses. For a fungal pathogen like R. solani AG8, which is unable to penetrate the roots of WT plants (16), mROS could contribute to the oxidative cross-linking of the cell wall to help prevent fungal penetration (31,32). Moreover, some evidence suggests that signaling may be the primary role of ROS in R. solani resistance because resistant transgenic cotton seedlings exhibited a rapid induction of ROS and downstream defense-related genes (33).…”
Section: Identification Of An Arabidopsis Mutant With Altered Stress mentioning
confidence: 99%
“…Beside a direct antimicrobial effect (review by Heath 2002), H 2 O 2 stimulates peroxysomes, activates defence genes, and stimulates numerous modifications of plant cell walls, i.e. oxidative cross-linking of phenolic compounds in the process of lignification (Baker and Orlandi 1995;Hammond-Kossack and Jones 1996;Mellersh et al 2002). As phenolic compound accumulation was detected in our study at the site of pathogenic hyphae penetration, this reaction seems to belong to triticale defense system against M. nivale.…”
Section: Discussionmentioning
confidence: 61%